Implantation of a Right Ventricular Implantable Cardioverter-Defibrillator Lead in the Right Ventricular Outflow Tract in a Patient with Ebstein Anomaly and Right Ventricular Lead Dislocation - Pecha, Simon; Yildirim, Yalin; Hahnel, Fabian; Reichenspurner, Hermann; Aydin, Muhammed Ali (The Thoracic and Cardiovascular Surgeon, 2014)
An 80-year-old patient with Ebstein anomaly and prior implantable cardioverter-defibrillator (ICD) implantation was sent to our heart center because of right ventricular (RV)-ICD lead dislocation. Positioning of the new RV lead was difficult, no stable position could be found, and sensing and threshold measurements showed weak results in the RV basis, apex, and septum. So, we conducted positioning of the lead in the RV outflow tract where a stable position with good sensing and threshold parameters was found.
Keywords: pacing; congenital heart disease; CHD